(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2019)
The root bark of Lonchocarpus eriocalyx was dried, powdered and extracted using chloroform, methanol and hot water. The extracts exhibited antibacterial activity against Pseudomonas aeruginosa, Escherichia coli and Staphylococcus aureus and antifungal activity against Saccharomyces cerevisiae. The decoction (100mg/ml) was more active than the chloroform and methanol extracts against the four microorganisms. Chromatographic fractionation of the chloroform extract using normal phase silica yielded the phytosterols lupeol and lupenone. At 100 mg/ml, the compounds were active against all the four microorganisms, with lupeol being more active than lupenone. This is the first report of the isolation of lupenone from Lonchocarpus eriocalyx.